Uji Daya Hambat Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) Terhadap Bakteri Staphylococcus epidermidis - Susi Novaryatiin; Anggun Meilani Pratiwi; Syahrida Dian Ardhany (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Kalimantan is an island in Indonesia the famous for biodiversity. The wealth of knowledge of traditional medicine by using plants from generation to generation in Kalimantan is also very much. Ethnic groups in Kalimantan use various types of plants for traditional medicine in natural habitat. One of the plants typical of Borneo was efficacious as traditional medicine was Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.). This study aims to determine the ability of inhibitory power of Bawang Dayak ethanol extract inhibiting the growth of Staphylococcus epidermidis bacteria. Inhibitory test results indicate that Bawang Dayak ethanol extract was able to inhibit the growth of Staphylococcus epidermidis bacteria at concentration 1%, 5% 10% dan 15% with inhibition zones were 16.9±3.6 mm; 17.6±1.8 mm; 18.6±0.0 mm; and 18.4±0.4 mm, respectively.